A New Enzyme-Linked Immunosorbent Assay for a Total Anti-T Lymphocyte Globulin Determination: Development, Analytical Validation, and Clinical Applications. Issue 3 (June 2017) - Montagna, Michela; La Nasa, Giorgio; Bernardo, Maria E.; Piras, Eugenia; Avanzini, Maria A.; Regazzi, Mario; Locatelli, Franco
Abstract : Background: Anti-T lymphocyte globulin (ATLG) modulates the alloreactivity of T lymphocytes, reducing the risk of immunological posttransplant complications, in particular rejection and graft-versus-host disease, after allogeneic hematopoietic stem cell transplantation (HSCT). We developed and validated a new enzyme-linked immunosorbent assay (ELISA) method to measure serum levels of total ATLG and evaluate the pharmacokinetics (PK) of the drug in children with β-Thalassemia, receiving allogeneic HSCT. Methods: Diluted serum samples were incubated with Goat-anti-Rabbit IgG antibody coated on a microtiter plate and then, with Goat-anti-Human IgG labeled with horseradish peroxidase. After incubation and washings, substrate solution was added and absorbance was read at 492 nm. ATLG concentrations in samples were determined by interpolation from a standard curve (range: 200–0.095 ng/mL), prepared by diluting a known amount of ATLG in phosphate-buffered saline (PBS). Low, medium, and high-quality control concentrations were 1.56, 6.25, and 25 ng/mL, respectively. This method was developed and validated within the acceptance criteria in compliance with the Guidelines for a biological method validation: the sensitivity of the method was 0.095 ng/mL. We analyzed serum samples from 14 children with β-Thalassemia who received ATLG (Grafalon) at a dose of 10 mg/kg administered as intravenous (IV) infusion on days −5, −4, and −3 before HSCT (day 0). Blood sampling for PK evaluation was performed on days −5, −4, and −3 before and after drug infusion; and then from day −2 to +56. Results: The median total ATLG levels pre-IVand post-IV were 0 and 118 mcg/mL on day −5; 85.9 and 199.2 mcg/mL on day −4; 153 and 270.9 mcg/mL on day −3, respectively. The median PK values of CL was 0.0029 (range: 0.0028–0.0057) L·kg −1 ·d −1, Vd was 0.088 (range: 0.025–0.448) L/kg and t1/2 was 20.2 (range: 5.8–50.2) days. Conclusions: These data suggest that given the marked interindividual variability of total ATLG disposition, the development of a validated ELISA method and the possibility to measure PK parameters in paediatric populations are essential steps to optimize drug therapeutic regimens.